2012
DOI: 10.1111/j.1399-3054.2012.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of the synthesis of ‘stress’ ABA by (+)‐[2H6]ABA infiltrated into leaves of Commelina communis

Abstract: The 'fettered' fraction of abscisic acid (ABA) that is held within the chloroplasts of unwilted bean and Commelina communis leaves is released when the leaves wilt and it is this 'free' ABA that is now proposed to cause the stomata to close within 2 or 3 min, well before the rise in total ABA can be detected. The large increase in 'stress' ABA begins 2-3 h later. The fettered ABA in a centrifuged homogenate is released by hyperosmotic solutions of mannitol (0.8 M) and NaCl (0.4 M). Dilute solution of halothane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Alternative explanations, including the release of ABA from internal stores (Georgopoulou & Milborrow ) or the hydrolysis of the conjugate ABA‐GE (Dietz et al ), cannot explain our observations of rapid increases in foliar ABA levels in angiosperms in response to increased VPD. While not relevant for stomatal responses to VPD transitions, the release of fettered‐ABA from the chloroplasts may play a major role in triggering the substantial biosynthesis of foliar ABA levels when plants are drought stressed beyond turgor loss point (Loveys ; Pierce & Raschke ; Georgopoulou & Milborrow ). Our data on ABA‐GE levels, though, indicate that the hydrolysis of ABA‐GE to ABA is only ever likely to contribute to a very small portion of increased ABA levels during water stress.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Alternative explanations, including the release of ABA from internal stores (Georgopoulou & Milborrow ) or the hydrolysis of the conjugate ABA‐GE (Dietz et al ), cannot explain our observations of rapid increases in foliar ABA levels in angiosperms in response to increased VPD. While not relevant for stomatal responses to VPD transitions, the release of fettered‐ABA from the chloroplasts may play a major role in triggering the substantial biosynthesis of foliar ABA levels when plants are drought stressed beyond turgor loss point (Loveys ; Pierce & Raschke ; Georgopoulou & Milborrow ). Our data on ABA‐GE levels, though, indicate that the hydrolysis of ABA‐GE to ABA is only ever likely to contribute to a very small portion of increased ABA levels during water stress.…”
Section: Discussionmentioning
confidence: 69%
“…During an increase in VPD, increased flux, driven by a higher transpiration rate, leads to the concentration of root-sourced ABA around the guard cells causing stomata to close (Tardieu & Davies 1993). As an alternative to the flux model, stomatal responses to changes in VPD have also been attributed to the rapid release of fettered-ABA from internal stores in the leaf (Georgopoulou & Milborrow 2012), most likely held in the chloroplasts (Loveys 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have shown that stomatal responses to changes in humidity or VPD in angiosperms are driven by functionally significant changes in foliar ABA level; this is particularly evident in angiosperm herbs ( McAdam and Brodribb 2015 ). Previously, some have argued that ABA responsible for the rapid (<1 h) responses of stomata to changes in water status does not have an origin in de novo synthesis but rather release from internal stores in the chloroplasts ( Georgopoulou and Milborrow 2012 ) or via a single step that converts the catabolite ABA–glucose ester to ABA ( Lee et al . 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABA plays a major role in regulating stomatal responses to VPD in angiosperms, as evidenced by the wilty phenotypes of ABA biosynthetic and signaling mutants at high VPD, combined with significantly impaired stomatal responses to increased VPD in sextuplet ABA-receptor mutants and mutants in the key ABA signaling gene OPEN STOMATA1 ( OST1 ) [ 31 , 32 ]. The speed of the stomatal response to VPD has previously led to the suggestion that ABA levels rise rapidly due to the release of fettered ABA [ 33 ], by the single-step hydrolyzation of stored, conjugated ABA–glucose ester (ABA–GE) [ 34 , 35 ]. While this hydrolysis pathway appears important for plants to respond to sustained dehydration stress [ 35 ], it does not appear to play a significant role in fast VPD responses across diverse angiosperm species, as ABA–GE levels do not change sufficiently, or even in the right direction (i.e., decrease) in some species, to account for the rapid increase in ABA levels under transient (20 min) VPD transitions [ 21 ].…”
Section: Aba-mediated Humidity Responses In Angiospermsmentioning
confidence: 99%